Current and Future Digital Trends in ELT. (August 2018) - Hockly, Nicky; Dudeney, Gavin
Anybody who has lived through the past decade of technological developments will know how quickly our world is changing. And what happens outside our teaching contexts, out there in the real world, will inevitably – at least some of it – end up having an impact on what we do inside our classrooms, lecture halls, schools and colleges. Some of the technologies we mention below will assuredly come to have an impact on some teachers and teaching contexts, others may simply burn brightly and disappear, as so often happens in the field. We start this article by looking at the bigger picture of technologies in society and in education – the context into which technology fits, with a focus on how the digital divide affects the implementation of educational technologies (or 'EdTech'). We then consider different and new ways and approaches to teaching and learning, before focussing on some of the new technologies which are – or will be – having an impact on what we do on a daily basis. In each case we reflect on how these new developments will continue to affect English language teachers and learners.